Tuning magnetic anisotropy of amorphous CoFeB film by depositing on convex flexible substrates - Qiao, Xinyu (2016)
We have investigated the magnetic properties of amorphous Co40Fe40B20 (CoFeB) thin filmsgrown on flexible polyimide (PI) substrates, which were fixed on convex molds with different curvatures during the magnetron sputteringdeposition. When the flexible substrates were changed from convex to flat state after fabrication, a uniaxial magnetic anisotropy was induced in the CoFeB film due to magnetostrictive effect. Furthermore, the anisotropy also depends on the thicknesses of the film and substrate. Our results demonstrate a convenient method to tune the anisotropy of magnetic thin filmsgrown on flexible substrates.